2009
DOI: 10.1007/s11355-009-0073-8
|View full text |Cite
|
Sign up to set email alerts
|

Responses to nonaeration and/or salinity stress in hydroponically cultured Populus nigra and Populus alba cuttings

Abstract: Growth, photosynthesis, and Na ? , K ? , Ca 2? , and Mg 2? distributions were examined in two-year-old hydroponically cultured Populus nigra and Populus alba cuttings exposed to salt stress (0, 50, or 100 mM NaCl) for four or six weeks and to nonaeration stress for one or three weeks, followed by a three-week aeration period in 2/ 5 Hoagland solution. Salt stress with 100 mM NaCl totally inhibited height increase in P. nigra cuttings. Combined salinity and nonaeration inhibited height increase to a greater deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…The first symptoms of salt stress that we noticed in this study were the edges of the leaf blade drying out, and older leaves dropping. Mao et al (2010) also observed drying of the tips and edges of the leaf blade, and a significant loss of leaves (up to 50%) of two-year-old black poplar plants treated for four weeks with 100 mM NaCl solution. Significant differences in susceptibility to salt stress were found in various species of poplars, in the form of growth inhibition and leaf damage, as well as physiological disorders related to metabolic functions (Chen and Polle 2010;Polle and Chen 2015;Sixto et al 2005).…”
Section: Discussionmentioning
confidence: 85%
“…The first symptoms of salt stress that we noticed in this study were the edges of the leaf blade drying out, and older leaves dropping. Mao et al (2010) also observed drying of the tips and edges of the leaf blade, and a significant loss of leaves (up to 50%) of two-year-old black poplar plants treated for four weeks with 100 mM NaCl solution. Significant differences in susceptibility to salt stress were found in various species of poplars, in the form of growth inhibition and leaf damage, as well as physiological disorders related to metabolic functions (Chen and Polle 2010;Polle and Chen 2015;Sixto et al 2005).…”
Section: Discussionmentioning
confidence: 85%